A batalha de Erechim ou de Erexim? Gatos à Paisana: A representação da nomenclatura Erechim ou Erexim em Gladstone Osório Mársico (TEL Tempo, Espaço e Linguagem, 2022)
The article analyzes the representation of the discussion for the official nomenclature of the city of Erechim, in the satirical book Undercover Cats, and in the text, The Battle of Erechim or of Erexim? by the satirical writer from Erechin, Gladstone Osório Mársico (1927-1976). The proposal is to analyze the representation of the discussion of the nomenclature of this city located in the interior of Rio Grande do Sul around the 1950s and that lasted until the 1970s, based on the representation in the text The Battle of Erechim or of Erexim? Published in 1975 in Veja magazine, and in the literary work Undercover Cats, published in 1962 by Editora Sulina. The study, in theoretical and methodological terms, dialogues with Cultural History and is situated on the border between Literature and History. The crossing of sources includes a bibliographic review, an oral source and uses Roger Chartier's concept of representations for the analysis.